BRAINSTORMING AS AN EFFECTIVE STRATEGY TO IMPROVE STUDENTS' WRITING SKILLS - Nengah Dwi Handayani; Ida Bagus Nyoman Mantra (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2022)
Writing is an important language skill that needs to be developed continuously and intensively to enhance the student's language competence. This study used a classroom action research design conducted in two cycles of learning activities to improve students' writing skills through a brainstorming strategy. This study was conducted in an EFL classroom, and the essential collection was done by administering a pretest, posttests, and a questionnaire. The results showed that the student's writing skills improved significantly in the first and second learning cycles compared to the pretest result. Therefore, the brainstorming strategy is considered to be a very effective strategy to be implemented in the writing classroom. This study suggests that teachers should consider using the brainstorming strategy to improve students' writing skills.